The Use of Rasch Model in Analyzing Grade V Elementary School Mathematics Items - Aqida, Debbi Silvia; Destia Khairunisa; Meisya, Rovika; Jannah, Raudhatul (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
This study was conducted to analyze the items used to measure students' mathematical abilities in a private elementary school in Pekalongan. There were 22 fifth-grade students involved in the study. The test items consisted of 15 multiple-choice questions related to the topics of spatial calculations and data presentation. The Rasch model was used to determine the fitness of these test items. The analysis was carried out using the Winsteps software. Test items were considered fit for the model in the Winsteps program if the Outfit MNSQ value ranged from 0.5 to 1.5, the Outfit ZSTD value was between -2 and 2, and the Pt-measure Corr value was positive, indicating that the item was a good fit for the model (Sumintono & Widiharso, 2015:98). The Winsteps program's output revealed that 15 test items were in accordance with the Rasch model, with an Outfit MNSQ value of 1.03. The Outfit ZSTD value was 0.0. Additionally, 11 test items had a positive Pt-measure Corr, while 4 test items had a negative Pt-measure Corr, indicating that these 4 items did not fit the model. Keywords: Item analysis, Rasch Model, Winstep.